The Climate-Smart Agriculture (CSA) Compendium - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The Compendium is at the end of proof of concept stage. In 2017, we built a beta-dashboard and cleaned about half the data. Analytic routes doing the basic analysis of effect size as well as bringing in historic and future climate information are already available.